Typology of crime constructions in the American TV series "Suits" - Bykhovets, Ye. V. (Видавництво НДУ ім. Миколи Гоголя, 2018)
The article suggests the definition of construction and approaches to classifying constructions in modern English. This research is based on the theoretical foundations of a constructionist approach to language analysis postulating that any linguistic pattern consisting of morphemes, words, partially lexically filled phrases like testify against somebody are constructions. Being generally defined as symbolic entities in which a particular meaning or function is associated with a particular form, constructions some aspect(s) of its form and function which is not strictly predictable from its component parts. The results of the analysis demonstrate that constructions about people, actions and instruments are the most numerous groups in the American television series "Suits". The paper proves that the use of constructions is constrained by the type and genre of discourse.
Keywords: construction; crime constructions; detective film